Banks' exposure to interest rate risk, their earnings from term transformation, and the dynamics of the term structure - Christoph Memmel (Deutsche Bundesbank, 2010)
We use a unique dataset of German banks' exposure to interest rate risk to derive the following statements about their exposure to this risk and their earnings from term transformation. The systematic factor for the exposure to interest rate risk moves in sync with the shape of the term structure. At bank level, however, the time variation of the exposure is largely determined by idiosyncratic effects. Over time, changes in earnings from term transformation have a large impact on interest income. Across banks, however, the earnings from term transformation do not seem to be a decisive factor for the interest margin.
Keywords: G11; G21; 330; interest rate risk; term transformation; interest income; Bankrisiko; Zinsrisiko; Zinsstruktur; Kreditgeschäft; Laufzeit; Zinsspannenrechnung; Schätzung; Deutschland